Predictors of Compliance with Free Endoscopic Colorectal Cancer Screening in Uninsured Adults - Anderson, Joseph C. (Springer-Verlag, 2011)
BACKGROUND: National guidelines endorse colonoscopy as the only colorectal cancer (CRC) screening test which prevents CRC and evaluates the entire large bowel. However, little is known regarding patient compliance with a screening program that exclusively uses colonoscopy, particularly in an underserved population. The Connecticut Department of Public Health provided funds for the total cost of colonoscopies, patient navigators and education of staff and primary care providers. With cost and provider barriers removed, we were able to examine patient related factors influencing compliance with colonoscopy in an ethnically diverse sample of underinsured adults. OBJECTIVE: To determine what patient related factors are predictors of compliance with screening colonoscopy. DESIGN: Cross sectional retrospective study. PARTICIPANTS: Underinsured patients (50–64 years) visiting nine Connecticut community health centers (CHCs) were evaluated for medical eligibility for screening; eligible patients were offered a free colonoscopy. MAIN MEASURES: Patients were deemed non-compliant if they refused, canceled or did not show for the colonoscopy. Obesity (Body Mass Index ≥ 30), educational attainment, gender, race, ethnicity, previous screening and social ties were examined as primary risk factors for compliance. KEY RESULTS: Of 424 uninsured patients (62% female, 21% White, 26% Black, 53% Hispanic), 354 were eligible for colonoscopy. Among eligible patients, 263 (74.3%) were compliant. Obese patients were more likely than non-obese patients to be non-compliant with colonoscopy (adjusted odds ratio = 2.16; 95% Confidence interval = 1.20-3.89). A high school education was positively correlated with increased compliance social ties such as having a spouse, significant other, family or friend also increased compliance. CONCLUSIONS: In an ethnically diverse, uninsured population, obese patients and patients with lower educational attainment were less likely to comply with free colonoscopy. These patients require special attention in colonoscopy-based CRC screening efforts.